2013
DOI: 10.1001/jamainternmed.2013.627
|View full text |Cite|
|
Sign up to set email alerts
|

Characteristics of Oncology Clinical Trials

Abstract: Clinical trials are essential to cancer care, and data about the current state of research in oncology are needed to develop benchmarks and set the stage for improvement. Objective: To perform a comprehensive analysis of the national oncology clinical research portfolio. Design: All interventional clinical studies registered on ClinicalTrials.gov between October 2007 and September 2010 were identified using Medical Subject Heading terms and submitted conditions. They were reviewed to validate classification, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
79
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 155 publications
(85 citation statements)
references
References 34 publications
(45 reference statements)
3
79
0
Order By: Relevance
“…Bradford et al found that 41.8% of trials were funded primarily by the industry [25], which corresponds with the 51.9% in our study. A reason for concern should be the lack of industrial funding for research beyond forms of systemic therapy.…”
Section: Discussionsupporting
confidence: 84%
“…Bradford et al found that 41.8% of trials were funded primarily by the industry [25], which corresponds with the 51.9% in our study. A reason for concern should be the lack of industrial funding for research beyond forms of systemic therapy.…”
Section: Discussionsupporting
confidence: 84%
“…One such example was a recently published cross-sectional study of oncology research that found that more than 25,000 outcomes had appeared only once or twice in oncology trials [2]. Furthermore, key outcomes may go unreported, and a review of missing data in Cochrane Reviews found that 102/143 (71%) reviews were unable to obtain the findings for key outcomes in the included trials, and 26 (18%) were missing data for more than half the patients on the review's pre-specified primary outcome [3].…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this view, oncology trials constitute the largest clinical discipline across all ClinicalTrials.gov registrations (11). Likewise, oncology trials comprise the largest subset of ClinicalTrials.gov registrations within Duke Medicine.…”
Section: Protocol Review and Monitoring System (Prms)mentioning
confidence: 89%